2006
DOI: 10.1186/1742-4690-3-12
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular assembly and budding of the Murine Leukemia Virus in infected cells

Abstract: Background: Murine Leukemia Virus (MLV) assembly has been long thought to occur exclusively at the plasma membrane. Current models of retroviral particle assembly describe the recruitment of the host vacuolar protein sorting machinery to the cell surface to induce the budding of new particles. Previous fluorescence microscopy study reported the vesicular traffic of the MLV components (Gag, Env and RNA). Here, electron microscopy (EM) associated with immunolabeling approaches were used to go deeply into the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Although intracellular particle assembly was initially thought to be a unique feature of macrophages, similar studies reporting localization of HIV-1 Gag and virions in intracellular CD63 + and/or Lamp1 + compartments in fibroblast, epithelial, and T-lymphocyte cell lines, as well as immunoprecipitation of extracellular virions with CD63 antibodies, have extended this notion, leading to the proposal that HIV-1 assembly is initiated on endosomal membranes in all cell types [8–13]. Moreover, several other works have reported the observation of murine leukemia virus and human T-cell leukemia virus type-1 particles in late endosomes [12,1417], suggesting that assembly in late endosomes is a general feature of retroviruses.…”
Section: Introductionmentioning
confidence: 99%
“…Although intracellular particle assembly was initially thought to be a unique feature of macrophages, similar studies reporting localization of HIV-1 Gag and virions in intracellular CD63 + and/or Lamp1 + compartments in fibroblast, epithelial, and T-lymphocyte cell lines, as well as immunoprecipitation of extracellular virions with CD63 antibodies, have extended this notion, leading to the proposal that HIV-1 assembly is initiated on endosomal membranes in all cell types [8–13]. Moreover, several other works have reported the observation of murine leukemia virus and human T-cell leukemia virus type-1 particles in late endosomes [12,1417], suggesting that assembly in late endosomes is a general feature of retroviruses.…”
Section: Introductionmentioning
confidence: 99%
“…However, approximately 8–17% of viruses do appear to have been labeled by the dyes. This does not come as a complete surprise since it has been previously documented that a small fraction of MLVs are released through the endosomal pathway rather than budding at the cell surface and these viral particles might take up dye more efficiently than virus budding at the cell surface 66 , 67 . This would suggest that these dual-stained retroviruses share even greater biochemical similarities to small EVs, which are mostly comprised of exosomes 17 .…”
Section: Discussionmentioning
confidence: 90%
“…To obtain further clues of the different roles of CHMP1A and CHMP1B in MLV virus propagation, we performed infectivity studies. Previous studies demonstrated that maturation inside the immature MLV virion is required for infectivity [ 26 , 38 , 39 ]. Accordingly, the yield of extracellular virions might not be a mandatory indicator of virus infectivity.…”
Section: Resultsmentioning
confidence: 99%